ANALYSIS OF IMPLEMENTATION 5C ASPECTS ON BANKING CREDIT DISTRIBUTION IN BATAM - Ikhwan, Nuzul; Raymond, Raymond; Lestari Siregar, Dian (EDUTECH CONSULTANT, 2017)
Credit disbursement by banks to SMEs in each region is determined by some benchmarks. One of the benchmarks is the evaluation of the feasibility of SMEs who will get the credit. Feasibility of credit disbursement can be carried out with 5 C aspects, which include: character, capacity, capital , colleteral and condition of economy. By using analysis of Cochran Q test, this study objects to identify the Bank Perkreditan Rakyat (BPR) in Batam related with implementation of 5C aspects the credits disbursement of SMEs and to identify the most dominant 5C variables as the determinant in the credit disbursement of SMEs in Batam. Results of this study found the presence of Implementation for all 5C variables in the banking credit disbursement in Batam. Also, conviction, responsibility and commitment of payment are the preliminary character’s information of SMEs who can receive the banking credit disbursement as the medium of SMEs’ construction to apply for the banking’s credit for business in Batam.